INTERNATIONAL CONVENTION OBLIGATIONS AS IMPORTANT FACTOR IN REFORMING THE LEGAL REGULATION OF ADMINISTRATIVE LIABILITY FOR VIOLATION OF LABOR LEGISLATION IN UKRAINE - Lavronova, Ivanna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is analyzing the conventions of the International Labor Organization ratified in Ukraine, to study harmonization of the current legislation of Ukraine in the field of labor relations in accordance with international requirements, the possibility of applying international legal norms in labor legislation of Ukraine in order to reform according international standards, is considering conventional obligations in the field of labor law as an important factor in reforming the legislation on administrative liability for violation of labor legislation, is indicating categories of violations of international norms in the field of labor, for which administrative responsibility is born, are identified inconsistencies and aspects of imperfect implementation of European standards in national legislation, and are proposed possible ways to amend administrative regulation in order to ensure compliance with the requirements of international standards of labor relations. Results: an important modern trend in the development of labor law in Ukraine is the harmonization of national and international legal norms. Therefore, reforms of labor legislation are carried out to take convention obligations into account and implement the international norms of labor law into national normative legal acts. The wide scope of labor relations regulation by the ILO determines the direction of reforming national labor legislation based on international norms of labor law. Conventional obligations in Ukraine are an important factor in the reform of labor law in terms of administrative responsibility for violations of labor legislation and the implementation of international norms to prevent administrative violations of labor legislation in Ukraine. Discussion: identifying problems with the implementation of international conventions in the labor field as the most important figure in the development of current labor legislation in Ukraine.